The Shiga toxin 2 B subunit inhibits net fluid absorption in human colon and elicits fluid accumulation in rat colon loops. - Pistone Creydt, Virginia (2004)
Shiga toxin (Stx)-producing Escherichia coli (STEC) colonizes the large intestine causing a spectrum of disorders, including watery diarrhea, bloody diarrhea (hemorrhagic colitis), and hemolytic-uremic syndrome. It is estimated that hemolytic-uremic syndrome is the most common cause of acute renal failure in infants in Argentina. Stx is a multimeric toxin composed of one A subunit and five B subunits. In this study we demonstrate that the Stx2 B subunit inhibits the water absorption (Jw) across the human and rat colonic mucosa without altering the electrical parameters measured as transepithelial potential difference and short circuit current. The time-course Jw inhibition by 400 ng/ml purified Stx2 B subunit was similar to that obtained using 12 ng/ml Stx2 holotoxin suggesting that both, A and B subunits of Stx2 contributed to inhibit the Jw. Moreover, non-hemorrhagic fluid accumulation was observed in rat colon loops after 16 h of treatment with 3 and 30 ng/ml Stx2 B subunit. These changes indicate that Stx2 B subunit induces fluid accumulation independently of A subunit activity by altering the usual balance of intestinal absorption and secretion toward net secretion. In conclusion, our results suggest that the Stx2 B subunit, which is non-toxic for Vero cells, may contribute to the watery diarrhea observed in STEC infection. Further studies will be necessary to determine whether the toxicity of Stx2 B subunit may have pathogenic consequences when it is used as a component in an acellular STEC vaccine or as a vector in cancer vaccines.